Potensi Zeolit di Daerah Sangkaropi-Mendila, Tana Toraja, Sulawesi Selatan - Kartawa, Wawa; Kusumah, K.Darwin (Pusat Survei Geologi, 2006)
The parent rock of zeolite at the Sangkaropi-Mendila area is composed of altered lithic and glassy tuffs, which is included within Lamasi Volcanic of Oligocene age. The zeolit was originated from volcanic ash with involvement of hydrothermal process. It is indicated by the presence of hydrothermally altered minerals such as chlorite, epidote, clay mineral, carbonate and silica. Nineteen rock samples have been analysed for petrography, SEM, CEC, ASD, XRD, XRF and AAS. Petrographic and SEM analyses show that the types of zeolites are mordenite and heulandite. The mordenite is characterized by textures of rat's nest and fibres, while the heulandite has a blocky monoclinic crystal texture with CEC up to 108,43 meq/100 g. Only three samples of ASD and one sample of XRD treatment contain composition of mordenite. Results of the XRF analysis show contents of SiO2 (62,69%-81,03%), Al2O3 (9,90%-19,82%), CaO (0,10%-0,22%), Na2O (0,12%-4,32%), K2O (0,63%-6,88%) and LOI (1,26%-12,62%). A total resource of 168.480.000 tons of Sangkaropi-Mendila zeolite was identified within an area of 360.000 m², offering a good prospect to the sectors of fishery, agriculture, waste handling and other industry. Keywords : zeolite, mordenite, heulandite, Sangkaropi, Mendila